2016
DOI: 10.1007/978-3-319-42102-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Open Digital Business Ecosystems: A Pathway for Value Co-creation

Abstract: Part 3: Digital Business EcosystemsInternational audienceIndividual businesses enthuse over participating in the 4 “We Economy” era [1] through a digital business ecosystem (DBE). DBE is seen as a gateway for an individual company to penetrate new markets where new products, services, and highly personalized experiences are delivered to their customers. Despite the benefits of DBE, collaboration uncertainty is the main challenge for a company wanting to participate in a wider ecosystem. This paper presents an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Similarly, articles on value co-creation in DBEs focus on how partners collectively generate value. In these studies, issues identified as essential for value co-creation in DBEs include ereadiness (Herdon et al, 2012), capability assessment (Sun et al, 2016), value creation processes (Selander et al, 2010) and inter-network competitions (Tan et al, 2009). So far, in the value co-creation literature, the focus has been on customer engagement (e.g., Acharya, Singh, Pereira, & Singh, 2018;Kamboj, Sarmah, Gupta, & Dwivedi, 2018).…”
Section: Business Issues Themementioning
confidence: 99%
“…Similarly, articles on value co-creation in DBEs focus on how partners collectively generate value. In these studies, issues identified as essential for value co-creation in DBEs include ereadiness (Herdon et al, 2012), capability assessment (Sun et al, 2016), value creation processes (Selander et al, 2010) and inter-network competitions (Tan et al, 2009). So far, in the value co-creation literature, the focus has been on customer engagement (e.g., Acharya, Singh, Pereira, & Singh, 2018;Kamboj, Sarmah, Gupta, & Dwivedi, 2018).…”
Section: Business Issues Themementioning
confidence: 99%
“…Despite the benefits brought by DBE, uncertainties such as ineffective collaboration and capabilities alignment still occur among business organisations (Sun et al, 2016). These uncertainties are the impediments to value creation and co-creation among the business organisations in a DBE.…”
Section: Introductionmentioning
confidence: 99%
“…The model based on the role of architect or orchestrator (Pashkov & Pelykh, 2020;Kawohl, 2021) and the most sophisticated DBEs evolving towards platforms with a clear nature of networked markets (Parker et al, 2016). These artifacts are inclusive (Sun et al, 2016) so they have an open nature of participation, the reason why they are called Open Digital Business Ecosystems (ODBE). Being open, they have a multi-agent constitution (Senyo,et al, 2019b).…”
Section: T H E O R E T I C a L B A C K G R O U N Dmentioning
confidence: 99%